As sanções políticas no Direito Tributário Brasileiro - Alves, Marília Bezzan Rodrigues (2019)
The aim of the present dissertation is to systematize the existing discourse on political sanctions. For this purpose, we adopt the analytical hermeneutic method, expanded by the philosophical current of logic and semantic-structured constructivism. We started from the study of the theory of the legal norm, to enter the field of tax sanctions and the elements of the constitutional system relevant to the subject, which involve the tax competence and the sanctioning competence, as well as the constitutional principles that guarantee fundamental rights of the administrated. Based on this conceptual apparatus, we analyzed the semantic burdens attributed to the term “political sanction” by the Federal Supreme Court, which was responsible for creating the expression, by deriving the criteria used by the Supreme Court to identify them. We then addressed the meanings attributed by the doctrine in a semantic pragmatic analysis of the subject. Finally, we analyzed the political sanctions under the syntactic-pragmatic plan, in order to demonstrate their actions in the criteria of the dispositive primary, primary sancionatory and secondary norms, using the method of the “Tax Matrix Rules” (“Regra Matriz de Incidência Tributária”), in order to propose “modalities” of political sanctions (dispositive political sanction, sanctioning political sanction and procedural political sanction)